Microstructure evolution of beryllium with argon ion irradiation. (December 2017) - Liu, Pingping; Zhan, Qian; Hu, Wen; Jia, Yumei; Han, Wentuo; Yi, Xiaoou; Wan, Farong
Highlights: Microstructure of argon irradiated beryllium was investigated by TEM and STEM. Precipitates containing Fe/Al/Mn were observed and analyzed. Dislocation loops were induced by argon irradiation in beryllium. Distribution of argon bubbles was analyzed and swelling was discussed also. Abstract: Beryllium is planned to be used as a neutron multiplier in the Helium-cooled ceramic breeder (HCCB) test blanket module (TBM), which is the primary option of the Chinese TBM program. The characteristic of the microstructural change of beryllium under irradiation is an important factor contributing to the understanding of degradation of physical-mechanical properties of the material. Beryllium metal was irradiated with 100 keV Ar + ions to a dose of 1 × 10 21 /m 2 at room temperature. The microstructural change of Beryllium has been investigated using transmission electron microscopy (TEM). After the irradiation, a high density of black-dot-like defects were induced in the sample, some of which were resolved as small dislocation loops. Gas-filled bubbles with an average size of about 33.7 nm were observed. Ion irradiation induced swelling at room temperature was also discussed.